Implementing a New Diabetes Resource for Wisconsin Schools and Families - Angela Nimsgern, MPH; Jenny Camponeschi, MS (Centers for Disease Control and Prevention, 2005)
Background Diabetes is one of the most common diseases in the nation. Students with diabetes face the daily task of balancing food, physical activity, and medication to survive. Teachers and school personnel often lack the knowledge needed to assist them. Context An estimated 2647 schoolchildren in Wisconsin have diabetes. The Wisconsin Diabetes Prevention and Control Program frequently receives anecdotal reports from parents and diabetes educators on the care of children with diabetes in the schools; the program also manages requests for information on new diabetes-related equipment from school personnel. Methods A statewide workgroup convened to develop Children with Diabetes: A Resource Guide for Wisconsin Schools and Families, aimed at improving the school staff's knowledge of diabetes and its management and their awareness of the benefits of maintaining glucose control. Training sessions for school professionals were developed and conducted around the state. All attendees were asked to complete an evaluation of the training. In addition, the workgroup included an evaluation form with each guide distributed and conducted a follow-up survey on the impact of the guide and changes to school policies. Consequences Of the 762 people who attended training sessions, 631 (83%) completed the evaluation form. On questions about the training session's content, quality, organization, and appropriateness, responses averaged 4.42 points on a scale of 1 (poor) to 5 (excellent). More than 9713 resource guides were distributed to more than 1359 individuals; 58 recipients responded to the evaluation form included with the resource guide, with 57 (98%) of these indicating that they would recommend the guide to others. Preliminary results of the follow-up impact survey show that many positive changes have been implemented to improve the school environment for children with diabetes since the resource guide was implemented. Interpretation This model of working with school professionals, health care practitioners, parents, and community organizations to create a resource guide with accompanying training sessions can be used in other states to accomplish similar goals of increasing knowledge about diabetes and improving social and policy environments.